DETERMINANTS OF EMPLOYEESâ ATTITUDE TOWARD UNION MEMBERSHIP (Study Case In A Logistics Company In Indonesia) - Dewantoro, Ranggapati Siswara; Sobri, Riani Rachmawati; Syaebani, Muhammad Irfan (Journal of Indonesian Economy and Business, 2013)
This research examines the determinants of employeesâ attitude toward union membership.These factors are represented by job-related predictor such as; employeesâ jobdissatisfaction, job stress, and consultative managerial style. Apart from these job-relatedpredictor variables, the cultural orientation played a role in this research such as;individualism and collectivism both horizontal and vertical. After performing resgressiontesting, the result shows that almost all variables are affecting employeesâs attitude towardunion membership except horizontal collectivism variable.Keywords: work dissatisfaction, work stress, consultative managerial style, individualism,collectivism, employeesâ attitude toward union membership